Studies on the activities of antioxidant enzymes under induced drought stress in in vivo and in vitro plants of Macrotyloma uniflorum (Lam.) Verdc. - Murthy, Savitha M; Devaraj, V R; Anitha, P; Tejavathi, D H (Recent Research in Science and Technology, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-hansi-font-family:Calibri; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> Activities of glutathione reductase, guaiacol peroxidase, catalase and contents of ascorbic acid, Hydrogen peroxide were analysed in in vitro and in vivo plants of Macrotyloma uniflorum under Polyethylene glycol (PEG) induced drought condition. Water stress was induced in in vitro plants by supplementing the regeneration medium with PEG (Mol. Wt. 6000) at the concentrations ranging from 5 to 25% while in in vivo plants by watering PEG solution with the same concentrations. The activities of glutathione reductase and guaiacol peroxidase were increased under induced drought stress condition in both treated samples. On contrary, catalase activities were decreased. The contents of ascorbic acid and hydrogen peroxide were enhanced correspondingly as the concentration of the PEG increased from 5 to 25%. The role of antioxidant enzymes under water stress condition is discussed. Further, the feasibility of mining the novel genes of drought resistance from the in vitro plants of Macrotyloma uniflorum is highlighted.